Performance analysis of hydrogen fuel cell with two-stage turbo compressor for automotive applications - Nabeel Ahsan (17302705) (2021)
This paper discusses the numerical modeling of an automobile fuel cell system using a two-stage turbo-compressor for air supply. The numerical model incorporates essential input parameters for air and hydrogen flow. The model also performed mass and energy balances across different components such as pump, fan, heat-exchanger, air compressor and keeps in consideration the pressure losses across flow pipes and various mechanical parts. The compressor design process initiates with numerical analysis of the preliminary design of a highly efficient two-stage turbo compressor with an expander, as a single-stage compressor has several limitations in terms of efficiency and pressure ratio. The compressor’s design parameters were carefully studied and analyzed with respect to the highly efficient fuel cell stack (FCS) used in modern hydrogen vehicles. The model is solved to evaluate the overall performance of PEM FCS. The final compressor has a total pressure and temperature of 4.2 bar and 149.3°C, whereas the required power is 20.08kW with 3.18kW power losses and having a combined efficiency of 70.8%. According to the FC model with and without expander, the net-power outputs are 98.15kW and 88.27kW, respectively, and the maximum efficiencies are 65.1% and 59.1%, respectively. Therefore, it can be concluded that a two-stage turbo compressor with a turbo-expander can have significant effects on overall system power and efficiency. The model can be used to predict and optimize system performance for PEM FCS at different operating conditions. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2021.05.007